The Effectiveness of High-Intensity Interval Training (HIIT) in Enhancing the Aerobic Endurance of Karate Specialization Students at PKO FIK UNIMED - Ramlan Sahputera Sagala; Dicky Edwar Daulay; Mhd. Andri Fahrian; Ade Setiowati (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
The low aerobic endurance of karate specialization students often became an obstacle in maintaining performance during prolonged training and match simulations. This condition indicated the need for an effective and time-efficient training method that matched the intermittent physiological demands of karate. This study aimed to determine the effectiveness of high-intensity interval training in improving the aerobic endurance of Karate Specialization Students at the Coaching Education Program, Faculty of Sports Science, Universitas Negeri Medan. The study employed a quasi-experimental method using a one-group pretest-posttest design. The participants consisted of 20 karate specialization students selected through purposive sampling. Aerobic endurance data were collected using the multistage fitness test to estimate maximal oxygen uptake. The training program was implemented for six weeks with a frequency of three sessions per week. The results showed a significant increase in students’ aerobic endurance after the training intervention, indicated by improved maximal oxygen uptake scores in the posttest compared to the pretest. The findings confirmed that high-intensity interval training effectively enhanced aerobic endurance in karate specialization students. The novelty of this study lay in the application of high-intensity interval training within the context of university-level karate specialization learning, which had rarely been explored in previous studies.